L17A/F19A Substitutions Augment the α-Helicity of β-Amyloid Peptide Discordant Segment - Liang, Chu-Ting; Huang, Hsien-Bin; Wang, Chih-Ching; Chen, Yi-Ru; Chang, Chi-Fon; Shiao, Ming-Shi; Chen, Yi-Cheng; Lin, Ta-Hsien (PLOS ONE, 2016)
β-amyloid peptide (Aβ) aggregation has been thought to be associated with the pathogenesis of Alzheimer’s disease. Recently, we showed that L17A/F19A substitutions may increase the structural stability of wild-type and Arctic-type Aβ40 and decrease the rates of structural conversion and fibril formation. However, the underlying mechanism for the increase of structural stability as a result of the alanine substitutions remained elusive. In this study, we apply nuclear magnetic resonance and circular dichroism spectroscopies to characterize the Aβ40 structure, demonstrating that L17A/F19A substitutions can augment the α-helicity of the residues located in the α/β-discordant segment (resides 15 to 23) of both wild-type and Arctic-type Aβ40. These results provide a structural basis to link the α-helicity of the α/β-discordant segment with the conformational conversion propensity of Aβ.